Contractual Administrative Responsibility Arising From Illegitimate Use Of The Management Powers - اسماعيل, أحمد; محفوض, حسن (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The management, towards the contracting party in administrative contracts, have rights and powers unlike in civil contracts. The management has several powers in the administrative contract domain represented in the power to monitor and direct the implementation of the contract, amendment of the contracting party obligations without that party protesting that pacta sunt servanda as established in the civil law. It also has the power to apply penalties on the contracting party in case of breaching obligations; further, the management may terminate the contract prematurely or prior to completion of the subject works shall the continuation of the implementation of the contract shall contradict the public interest or shall the implementation of the contract became unproductive to the objective it was signed for. The management has the powers of the public utility and the obligation to ensure the concord of its traffic and supervising it in implementation of the public interest. Thus, the management practices such powers even if the contract did not state and without the need to seek jurisdiction. Based on the above, the management practice of such powers and privileges shall be considered of the distinguishing characteristics of the administrative contract and they represent the primary obligation required from the public authority based on the regulation of the public utility. The origin is that such practice shall not embed a failing or illegitimate feature by the management justifying the implementation of the public interest. Hence, the management needs to practice its powers within a framework of legitimacy that crossing the same shall be considered a mistake entailing its contractual liability.